Assessment Of Medication Adherence, Knowledge, And Health-Related Quality Of Life Among Atrial Fibrillation Patients Using Warfarin In Penang, Malaysia - Matalqah, Laila Mahmoud Ali (2014)
The use of oral anticoagulant therapy (OAC) has been a standard clinical practice to prevent stroke in patients with atrial fibrillation. In Malaysia, studies evaluating knowledge, non-adherence and quality of life among patients with chronic use of warfarin and their relationship with their anticoagulation control, are still recent and scarce. This PhD study aims to gain insight into the knowledge and adherence of atrial fibrillation patients in Penang state towards oral anticoagulant medication, to assess their pattern of health-related quality of life (HRQoL) as well as to investigate the relationship of the former studied variables with the anticoagulation control as measured by the International Normalized Ratio. This study also aims to explore other predictive factors that could potentially explain variations in INR values. A novel model described predictors of controlled INR values was developed.